Trans bodies: an essay on norms, singularities and political happening - Costa-Val, Alexandre; Guerra, Andréa (Saúde e Sociedade, 2019)
This essay intends to reflect on how sexuality has been circumscribed by some fields of knowledge, especially those related to medicine, and how this affects us in the current social context. Based on the assumption that we are immersed in a network of devices that are a condition of our own existence, we especially examine the experiences related to genres and sexualities that escape from the established normative framework, seeking to locate its political dimensions from some elements extracted from the elaborations of the psychoanalyst Jacques Lacan and the philosophers Judith Butler and Giorgio Agamben. We intend to keep on sight the question related to the modes of resistance and inventions that we can produce being within that network. We approached the subject revisiting some notions that were incorporated into the medical field – especially that of psychiatry – and then, more specifically, we analyzed some trans experiences that have occupied space in the mass media and social networks. These reports, when revealing something that escapes any attempt of normalization, will subsidize proposals of forms of the political, focusing on the singularities to provoke reflections that can (re)orient our practices in the everyday life.